It Takes a Village : Community Based Participatory Research as a Design Research Tool - Dhaundiyal, Dhriti; Pant, Richa (My University, 2020)
Design has transitioned progressively from a consumer-focused discipline to a human-centred one, with a more complex agenda. Design thinking has been successfully deployed as an agent for social change. In this paper we take a trans-disciplinary approach to social design in remote villages of Uttarakhand, India. Lack of employment opportunities and tough sustenance in the mountainous regions of India has led to mass migration and ghost villages. Recent interventions at the micro level, born from a participatory approach rather than the top down structure of government development schemes, have been seen to be more effective in tackling this complex socio-economic issue. Community based participatory research has been deployed previously in areas like public health and primary education successfully. With this paper we reflect on the viability of using it to identify areas of effective design intervention, not just to address current issues faced by the residents of remote villages in the Himalayas but also to encourage future social entrepreneurs. We worked in a group of Himalayan villages in collaboration with local government agents as part of a month long design education module. Design students and development professionals teamed up with residents, using methods like transect walks, socio-cultural mapping of health, water and sanitation, education, leadership, mobility, skill and vulnerability and co-design activities. Analysis led to a deeper understanding of social structure, education, resource equity, power dynamics, flow of information, drudgery, vulnerability and potential areas for social entrepreneurs. An iterative model of exploration, analysis, design proposition and refinement was followed to identify challenges faced by residents and areas of possible design intervention.
Keywords: Community Based Participatory Research; Social Design; Rural India; Design Education